2008
DOI: 10.1021/la801019d
|View full text |Cite
|
Sign up to set email alerts
|

Nonaqueous Nanoscale Metal Transfer by Controlling the Stickiness of Organic Film

Abstract: Nanoscale metal patterns were successfully reproduced on top of a functional organic layer by a direct metal-transfer technique (DMT). A gold film deposited on the protruding features of a stamp was transferred to the organic layer by controlling its stickiness through a two-step thermal treatment. The process was also suitable for the transfer of highly adhesive metal materials to the stamp surface by using an additional gold layer. Chromium nanowires at 70 nm half-pitch were faithfully produced without any d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…After detaching the glass stamp from the polymer layer (Figure 7d), fabrication of the organic memory devices with an 8 × 8 cross‐bar array and a junction area of 2 μm × 2 μm was completed. Lee et al109 also successfully fabricated nanoscale metal patterns for organic memory devices using the same technique. A DMT method featuring a two‐step thermal treatment was capable of transferring metal lines with a 70‐nm half‐pitch to an organic active layer.…”
Section: Strategies For Memory Applicationsmentioning
confidence: 99%
“…After detaching the glass stamp from the polymer layer (Figure 7d), fabrication of the organic memory devices with an 8 × 8 cross‐bar array and a junction area of 2 μm × 2 μm was completed. Lee et al109 also successfully fabricated nanoscale metal patterns for organic memory devices using the same technique. A DMT method featuring a two‐step thermal treatment was capable of transferring metal lines with a 70‐nm half‐pitch to an organic active layer.…”
Section: Strategies For Memory Applicationsmentioning
confidence: 99%
“…The three transfer-printing methods basically rely on the differences in adhesion to transfer NWs, metal films, and even entire NW devices from weakly adhesive donor substrates to more strongly adhesive receiver substrates when these two substrates are brought into close physical contact. Previously reported transfer-printing methods, such as microcontact printing, nanoscale-transfer printing, and metal transfer printing (16,(19)(20)(21)(22)(23), have been used mainly to transfer metal films to receiver substrates by using PDMS stamps. Our methods significantly broaden the transferred substances from metals to the entire NW devices with not only PDMS but also tapes.…”
mentioning
confidence: 99%
“…At a detachment temperature of 95 °C, the PdAu NRB array with uniform 15 nm nanogaps was faithfully transferred onto the PS substrate across the entire transfer area of 2.25 cm 2 (Figure S3, Supporting Information). We found that, at a detachment temperature of less than 80 °C, the transfer area of the PdAu NRB array was much smaller, which we attributed to the reduced stickiness of the polymer substrate . Finally, titanium (Ti) and Au were deposited through a shadow mask to create top‐contact electrodes for H 2 sensing (Figure e).…”
Section: Resultsmentioning
confidence: 99%